FORMULASI DAN UJI MUTU FISIK SABUN PADAT MENGANDUNG EKSTRAK LAVENDER (Lavandula angustifolia Mill.) DAN KULIT BATANG KAYU MANIS (Cinnamomum burmanii) - Sri Rezeki Samosir; Dina Maya Syari; Mawarni Atika Sari (Universitas Imelda Medan, 2026)
The manufacture of solid soap combination of lavender leaf & flower extract (Lavandula angustifolia Mill) and cinnamon bark extract (Cinnamomum burmanii) has been carried out. The research method is experimental in the laboratory with a quantitative analysis approach. The sample of this research is from lavender leaf & flower extract (Lavandula angustifolia Mill) and cinnamon bark extract (Cinnamomum burmanii). The research stages include making simplicia, evaporation extraction, phytochemical screening, making solid soap preparations and testing the physical quality of solid soap. The extraction stage uses the maceration method for 3 days with 96% ethanol solvent, the extract obtained using a rotary evaporator. Solid soap from a combination of lavender leaf & flower extract (Lavandula angustifolia Mill) and cinnamon bark extract (Cinnamomum burmanii) is made in 3 formulations, namely 1%, 2%, 3%. Physical quality testing includes organoleptic test, pH test, foam height test, water content test. The results of the organoleptic test showed a brown colored preparation and a solid texture with a distinctive cinnamon aroma. The results of the pH test showed a pH of 11 for all three formulas. The results of the foam height test showed an initial foam height of 6cm – 7cm and a final foam height of the three formulas of 1cm. The results of the water content test at (F1) 1.29%, (F2) 1.03% and at (F3) 1.86%. The results of the study can be concluded that the combination of lavender leaf & flower extract (Lavandula angustifolia Mill) and cinnamon bark extract (Cinnamomum burmanii) can be formulated as a solid soap preparation.